The impact of alerting designs on air traffic controller's eye movement patterns and situation awareness - Kearney, Peter; Li, Wen-Chin; Yu, Chung-San; Braithwaite, Graham (Taylor & Francis, 2018)
This research investigated controller’ situation awareness by comparing COOPANS’s acoustic alerts with newly designed semantic alerts. The results demonstrate that ATCOs’ visual scan patterns had significant differences between acoustic and semantic designs. ATCOs established different eye movement patterns on fixations number, fixation duration and saccade velocity. Effective decision support systems require human-centred design with effective stimuli to direct ATCO’s attention to critical events. It is necessary to provide ATCOs with specific alerting information to reflect the nature of of the critical situation in order to minimize the side-effects of startle and inattentional deafness. Consequently, the design of a semantic alert can significantly reduce ATCOs’ response time, therefore providing valuable extra time in a time-limited situation to formulate and execute resolution strategies in critical air safety events. The findings of this research indicate that the context-specified design of semantic alerts could improve ATCO’s situational awareness and significantly reduce response time in the event of Short Term Conflict Alert activation which alerts to two aircraft having less than the required lateral or vertical separation.
Keywords: Air traffic management; Alerting design; Eye movement patterns; Situation awareness; Visual attention